Pros and Cons oflnfusing FD I in the Indian E-commerce Industry - Kumar, Navdeep (Gyan Management Journal, 2016)
In a customer driven economy, the Indian e-commerce industry has registered substantial growth triggered by socio-economic drivers during last few years. This sector has emerged and expected as a significant contributor towards the economic growth of the country. Owing to the huge potential in the Indian market, the sector is set to scale new heights wit immense opportunities. Nevertheless, the industry is also fronting challenges in the path of future growth and survival. Insufficient capital in the Indian e-commerce industry is the vital issue of concern. The Indian government is thinking over permitting FD! in this industry. However, there are both favourable and adverse impacts of this decision on the domestic front. The present paper is an attempt to accentuate the diverse issues concerning crucial sector of the economy in the light of potential, challenges and future strategic course of action.